"La consulta previa en los comunidades campesinas mineras y su incidencia en el ejercicio de los derechos comunitarios constitucionales" - Alucho Guzmán, Francisca Ninapacari (2018)
The project aims to make the situation of the Prior Informed and Free Consultation based on its history, process, Law and Regulation, within the framework of International Human Rights Law, specific to Convention 169 of the International Labor Organization. The right to the Prior Consultation is an opportunity to listen to the ever-excluded voice of indigenous peoples. Through it the norms of international law as national have allowed to include in the public sphere the indigenous agenda. But having a law and regulation, as is the case in Ecuador, is not enough, as there is both the duty of the State to apply and explain in good faith the prior consultation to respect it and at the same time without generating false expectations, as well as determine the real magnitude of the same, as the intervening actors. The debate is fundamentally trapped because the Executive Branch considers that not all peasant communities have the same rights as indigenous peoples, while the jurisprudence of the Constitutional Court and national laws do raise this equivalence. In this sense, prior consultation in Ecuador is especially relevant, as it is this place where there are numerous mining investment projects, one of the most important engines of the Ecuadorian national economy. The objective of this project entitled "Prior consultation in peasant mining communities and their impact on the exercise of constitutional community rights" is to determine the real situation of protection and / or violation of the rights of peasant and native communities in the processes of prior consultation. In the country there is no culture of adequate protection of Rights. The lack of application to the right to collective constitutional participation in a process of a special and obligatory public character that must be done in advance when it is to be decided, to decide on a public or private project that will directly affect the forms of life of indigenous peoples in its territorial, environmental, cultural, spiritual, social, economic, health, and other aspects that affect its ethnic integrity. Keywords: Prior Consultation, Communities, Discrimination, Constitutional Law, international legal standards